Isotopic Poetics: The Petrocultural Appropriations of Lesley Battler’s Endangered Hydrocarbons - Karpinski, Max (Imaginations)

(untitled) (York University, 2022)
Lesley Battler’s Endangered Hydrocarbons (2015) broadens the scope of what might be considered a politicized ecopoetics. Battler’s collection, which I suggest works through a poetics of appropriation, links experimental poetic form with Anthropocene criticism in the humanities and critical studies of settler colonialism, addressing the contiguities between ecological degradation and land expropriation, while also making the appropriation of language one of its central formal concerns. In the context of the Canadian nation-state and its extractive economies, I argue that Battler’s “isotopic poetics” appears as a politically motivated formal praxis for working through the tangled exigencies of ongoing settler-colonial dispossession and the accelerating environmental crisis.